Facial cleanser made of Eleiodoxa conferta (Kelubi) extracts - Michelle, Lim May Yee (2015)
The study is undertaken to formulate anti-acne facial cleanser made of Eleiodoxa conferta extract and determine the stability and safety of the formulation. Different percentage of water extract of Eleiodoxa conferta comprised of 2.5%, 3.5%, 4.5% and 5% were incorporated into the facial cleanser base and in vitro antimicrobial well diffusion assay was performed on acne inducing bacteria, Propionibacterium acne, Staphylococcus aureus and Staphylooccus epidermis. All the formulations had no antimicrobial effect on the main acne causative bacterium which was Propionibacterium acne. Partial antimicrobial effect on Staphylococcus aureus and Staphylooccus epidermis were observed with partially clear zone of inhibition ranging from 10.1 mm to 48.1 mm. 3% of Eleiodoxa conferta facial cleanser formulation was selected to proceed with stability and safety test considering of the efficacy and cost of production of the product. No phase separation was observed when the facial cleanser formulation centrifuged at high speed for preliminary stability test. The formulation was unstable as colour changed had been observed and the antimicrobial strength against Staphylococcus aureus had reduced to 24.5 and 25.8 mm only, and effect on Staphylooccus epidermis was lost after storage for 28 days at three different temperatures of 4°C, 37°C and 45°C. Microbiological counts of the product before and after stability test were more than 10ᶟ, exceeded the limit set by the authority indicating that the preservative system of the formulation was ineffective. The heavy metals contents of the formulation detected using Flame Atomic Absorption Spectrometer (AAS) were below the permitted level, Pb 1.0685 ppm, Cd not detected, Zn 0.0565 ppm, Fe 0.4160 ppm and Cu 0.0285 ppm showed that the product will not causes heavy metal toxicities to the user. Further research to improve the stability of the personal care product made of Eleiodoxa conferta can be conducted.